Perbedaan Jumlah Trombosit Pada Teknik Pengambilan Darah Vena menggunakan Spuit Dan Vacumtainer - Bastian Darwin; Aristoteles; Dewi Hartati (IKesT Muhammadiyah Palembang, 2023)
Platelets are blood cells that play an important role in homepstatis. Platelets attach the endothelial layer of torn blood vessels (wounds) by forming a platelet plug. Platelets do not have a cell nucleus, measuring 1-4, and the cytoplasm is blue with purple-reddish granules. Platelets are derived from megakaryocytic, which are derived from the cytoplasm fragments of megakaryocytic. 150.000-350,000 platelets /ml of blood platelet granules contain blood clotting factors, Adenosine Diphosphate (ADP). Adenoxine Triphoxphate (ATP, calcium, serotonin, and catecholamines. Most of them play a role in stimulating the start of the blood clotting process. The lifespan of platelets in circulating blood is about 8-10 days. The purpose of this study was to determine differences in the number of platelets depending on the technique of taking venous blood using a syringe and a vacumtainer. The type of research used is cross sectional, which was carried out in the laboratory of Puskesmas Dempo on 05-01-2022. The sample used was EDTA blood. The number of samples studied was 30 samples with two treatments using a non-probability sampling technique. Based on the results of the examination of the number of platelets in the technique of taking venous blood using a syringe and a vacumtainer using the hematology analyzer, the average value for the syringe method was 353,27 /ml of blood and the vacumtainer method had an average value of 345,27 /ml 0f blood p= 0.612 was obtained from data analysis using the paired sample test. The conclusion of this study is that there is no difference between the number of platelets dependen on the technique of taking venous blood using a syringe and a vacum.